2003
DOI: 10.1029/2003jd003878
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modeling of meteorological conditions in the lower troposphere during a winter stratospheric ozone intrusion over Zagreb, Croatia

Abstract: [1] We investigated mesoscale meteorological conditions in the lower troposphere during an episode of winter stratospheric ozone intrusion over Zagreb, Croatia, on 6 February 1990. This particular event was associated with a jet stream over northwestern Europe, and it was accompanied by elevated ozone values at two measuring sites in the greater Zagreb area. A Eulerian nonhydrostatic prognostic mesoscale model has been employed to reproduce significant fine-scale features of the fold. The initial streamer of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…European urban monitoring networks and experimental campaigns have revealed that on the large scale, polluted air masses that were enriched by ozone over the Mediterranean were mostly advected in central Europe (Millan et al , ; Lindskog et al , ) by long‐range transport (Carvalho et al , ). Large‐scale meteorological processes can also create conditions favourable to the stratospheric intrusion of ozone (e.g., Klaić et al , ) that can result in a local increase in tropospheric ozone concentrations. While daytime ozone production is dominated by photochemical reactions, an increase in night time ozone levels is solely the result of specific wind circulation systems on local and regional scales (Strassburger and Kuttler, ).…”
Section: Introductionmentioning
confidence: 99%
“…European urban monitoring networks and experimental campaigns have revealed that on the large scale, polluted air masses that were enriched by ozone over the Mediterranean were mostly advected in central Europe (Millan et al , ; Lindskog et al , ) by long‐range transport (Carvalho et al , ). Large‐scale meteorological processes can also create conditions favourable to the stratospheric intrusion of ozone (e.g., Klaić et al , ) that can result in a local increase in tropospheric ozone concentrations. While daytime ozone production is dominated by photochemical reactions, an increase in night time ozone levels is solely the result of specific wind circulation systems on local and regional scales (Strassburger and Kuttler, ).…”
Section: Introductionmentioning
confidence: 99%
“…A three‐dimensional non‐linear non‐hydrostatic prognostic mesoscale model for unsaturated air (MEMO, version 6.0) is employed. A detailed model description and its performance have been documented in previous publications (Moussiopoulos, 1995; Caballero and Lavagnini, 2002; Klaić and Nitis, 2002; Klaić et al, 2002, 2003a) and here we provide only a brief overview. The model vertical coordinate is terrain following.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…A three-dimensional non-linear non-hydrostatic prognostic mesoscale model for unsaturated air (MEMO, version 6.0) is employed. A detailed model description and its performance have been documented in previous publications (Moussiopoulos, 1995;Caballero and Lavagnini, 2002;Klaić and Nitis, 2002;Klaić et al, 2002Klaić et al, , 2003a) and here we provide only a brief overview. The model vertical coordinate is terrain following.…”
Section: Numerical Modelmentioning
confidence: 99%